The equation of F(x) is F(x) = x³ - 3
Step-by-step explanation:
Let us revise the translation
∵ The graph of F(x) has the same shape as the graph of
G(x) but it is shifted down 3 units
- That means F(x) is the image of G(x) after translation 3 units down
∴ The graph of the function G(x) translated vertically down by 3 units,
to give the graph of F(x) = G(x) - 3
∵ G(x) = x³
∴ F(x) = x³ - 3
The equation of F(x) is F(x) = x³ - 3
Learn more:
You can learn more about the translation in brainly.com/question/2451812
#LearnwithBrainly